Perkembangan Senjata Laser LY-1 China dan Urgensi Ratifikasi Protokol IV CCW oleh Indonesia - Miftahur Rahmi; Danial; Hera Susanti (Unram Law Review, 2026)
The LY-1 laser weapon developed by China raises relevant legal issues within the framework of International Humanitarian Law (IHL), particularly in relation to the application of Protocol IV to the Convention on Certain Conventional Weapons (CCW). This study aims to analyze two issues: first, the extent to which the technical characteristics of China’s LY-1 laser weapon may be assessed under the prohibition standards set forth in Protocol IV of the CCW; and second, the legal implications arising from Indonesia’s status as a non-party to that instrument. This research employs a normative legal method with a treaty-doctrinal approach, namely an analysis of the authentic text of Protocol IV of the CCW combined with an examination of Article 36 of Additional Protocol I of 1977 as a parameter for the legal review of new weapons. The primary sources consist of treaty texts, official positions of the ICRC, doctrines of international humanitarian law, and publicly available technical specifications. The study identifies two key findings. First, the dual-use nature of the LY-1 system places it within a normative grey area under Article 1 of Protocol IV of the CCW. Applying the ICRC’s foreseeable effects approach, permanent blindness may be regarded as a reasonably foreseeable outcome, thereby weakening China’s claim that the system is solely intended for anti-sensor purposes. Second, Indonesia’s non-state party statusresults in a clear asymmetry of treaty obligations, limiting its legal standing to raise claims within CCW mechanisms, excluding it from normative development processes, and constraining its regional defense diplomacy. This research provides a distinct scholarly contribution by examining the legal consequences of this asymmetry in CCW Protocol IV membership. It compares China, as the developer of the LY-1 laser, with Indonesia, a non-party state.